Liquid crystal based optical switch - Seto Benjamin. (2009)
Photonic Crystal Fibers (PCFs) are characterized by an arrangement of micron-sized air holes running down the length of the fiber. The microstructure allows realization of the so-called index-guiding PCFs, which guide light in a high-index core using a principle similar to total internal reflection (TIR), and the Photonic Band Gap (PBG) guiding PCFs which can guide light in a low-index core. The unique properties of band gap guiding PCFs has opened the possibility of combining the classical fiber material, silica, with new materials having higher refractive index than that of silica, and create guided wave structures for confinement of light in silica In the thesis, PCF will be infiltrated with E7 nematic liquid crystals to create a Photonic Liquid Crystal Fiber (PLCF) and analyzed for tunable optical properties for manipulation of guided light. The first part of the thesis deals with the infiltration of the liquid crystal into the photonic crystal fibers. Experimental results based on the propagation properties after the infiltration are discussed. The second part of the Thesis deals with the development of a tunable light switch based on the PLCF. Experimental results on the propagation properties based on the influence of an external electric field will be discussed.